The out-of-field phenomenon: Perceptive consequences and Support Needs Through the Lens of graduating second career preservice teachers - Du Plessis, Anna; Wheeley, Elizabeth; Klieve, Helen; Gramotnev, Dmitri; Gramotnev, Galina; Park, Eunjae (Journal of University Teaching and Learning Practice, 2023)
Second career preservice teachers’ perceptions about the out-of-field teaching phenomenon might influence career decisions, such as retention and attrition. A target group of 133 second career graduating Master of Teaching students voluntarily participated in this mixed method study which offered findings through analysed open and Likert-scale questions and semi-structured interview data. The pilot offers new information about second career preservice teachers’ perceptions about their possible involvement in out-of-field teaching practices and the phenomenon’s implications for capabilities, skills knowledge, self-efficacy, support needs and professional identity. A critical reflection on quality teaching and teacher training programs, and preparation for the teaching profession form the foundation for further research in this field. The analyses further stimulate a deeper understanding of the future second career teaching workforce and perceptions of support resources.